How strong are streak artifacts in limited angle computed tomography? *The research is supported by the NSF grant DMS 1212125. (15th April 2015) - Nguyen, Linh V
Abstract: In this article, we consider the limited angle problem in computed x-ray tomography. A common practice is to use the filtered back projection with the limited data. However, this practice has been shown to introduce the artifacts along some straight lines. In this work, we characterize the strength of these artifacts.